Study of Loneliness and Identity Styles among Internet Addicted Students in Faculty of Engineering, Islamic Azad University, Central Tehran Branch - Bnirostam, Touraj; Saberi, Hayedeh (Ital Publication, 2017)
Application of new technologies is an obvious effects of today world. Internet as a newborn tool of contemporary technology world, plays an important role in change of people's life. Internet now is a necessary tool of modern era which makes it an inevitable component of everyday life. The present study aims to investigate level of sense of loneliness, identity styles and Internet Problematic Use among students. This is a descriptive survey study whose statistical population is all of the students of Technical - Engineering Faculties of Islamic Azad University in 1394-95 (2015-2016) in Tehran, using Multistage Cluster sampling method. 3 questionnaires, sense of loneliness, identity styles and internet addiction, have been selected for gathering data. Data analysis have been carried out by SPSS software. The results indicate that sense of loneliness is higher than two other variances which in turn end in internet addiction and identity disorders.